Serologically (tTG) Detected Celiac Disease Cases in Children with Down’s Syndrome - Ferdouse, Zannatul; Islam, Kazi Ashraful; Miti, Afsana Anwar; Alam, Sayeda Tabassum; Akhter, Shaheen; Rahman, Md Mizanur; Karim, Bazlul (Northern International Medical College Journal, 2018)
Background : Down’s syndrome (DS) is the most common chromosomal abnormality. Some autoimmune diseases are over represented in children with DS like insulin dependent diabetes mellitus, autoimmune thyroiditis and celiac disease (CD). Classical presentations of CD may be absent in children with Down’s syndrome. Worldwide different tests are available for the diagnosis of CD. Among these, tissue transglutaminase (tTG) is cost effective, sensitive and the only test available in Bangladesh. Objective : To ascertain the frequency of celiac disease and their clinical presentations in children with Down’s syndrome by doing serum tTG (IgA) level. Methods : A cross sectional study was carried out in the department of Paediatric Gastroenterology and Nutrition and Paediatric Neurology of Bangabandhu Sheikh Mujib Medical university (BSMMU ) Dhaka, Bangladesh. Blood samples of 30 consecutive cases of DS were taken for estimation of tissue transglutaminase (IgA) level and clinical features of all positive cases were also recorded. Result : Tissue transglutaminase (tTG) was detected in 10% cases of studied Down’s syndrome children. One third of patients, who had CD, had growth failure. Common features of associated CD cases were dirrhoea, vomiting and abdominal pain. Conclusion : Celiac disease was found in 10% of the studied cases of Down’s syndrome in the present study. Serological tests for celiac disease could be performed in all cases of Down’s syndrome whether it would be symptomatic or asymptomatic Northern International Medical College Journal Vol.9(1) July 2017: 271-273